A política de participação na educação de jovens e adultos no município de Belém (1997 - 2004) - ARAÚJO, José Carlos Ferreira (2006)
This work analyzes the Politics of participation in the Education of Youths and Adults (EJA) in the context of Brazilian capitalist development, focalizing the programs and the experiences implemented in the municipal district of Belém, State of Pará, during the period from 1997 to 2004. In the analysis we will privilege the relationships among the level macro (Calculation Partition and Congress of the City) and the level micron (PROALFA and MOVE) implemented by the City hall of Belém, that are known as patterns of instances characterized by the participation of the population in the discussion and elaboration of politics and development projects and the historical ransom of the experiences and programs executed in that teaching modality. It is still our intention to identify like SEMEC and other municipal organs were restructured, to create and to strengthen responsible sections for that teaching modality. In the investigative process we will use the research, of qualitative character. This way, to trace a panorama concerning the thematic the following procedures we used: bibliographical researches, documental researches. We will be using the conceptual categories of power-participation and of the controlled participation. To level macro, in spite of the progresses observed in the popular participation in Belém, one cannot affirm that the civil society has assumed the control about the municipal planning. It can be inferred that this happened in shared way between the municipal power and the civil society in which the organization and the dynamics of operation of the Calculation Partition and the Congress of the City allowed the decentralization of the decisions on the public politics that they started to happen inside of the Council of the City, maximum organ of decision in the Congress of the City. That was the way found by the Municipal Power of legitimating the participation of the civil society. PROALFA and MOVA were it part of the educational politics of the Government of the People and their political and cultural action is affirmed, getting important the partnership concept and dialogue among being able to public and civil society. The first paper of the Government of the People in relation to PROALFA and MOVA was to be placed as propeller of the creation and of the implement of the Movement, what was constituted as controlled participation, therefore it had origin in the government's concession. Those instances as the Calculation Partition and the Congress of the City and PROALFA and MOVA had their limitations, in the same way that is recognized that they are still very far away from a participation full massive – powerparticipation, because of its complex construction. But it is necessary to recognize that there was advance in the democratization process and decentralization in Belém, existing an enormous progress in the construction of public politics for that teaching modality.